The potential of Atorvastatin for chronic lung diseases therapy - Alaa S. Tulbah (Elsevier, 2020)
Atorvastatin (ATO) is of the statin class and is used as an orally administered lipid-lowering drug. ATO is a reversible synthetic competitive inhibitor of 3-hydroxy-3-methyl-glutaryl-CoA (HMG-CoA) reductase thus leading to a reduction in cholesterol synthesis. It has recently been demonstrated that ATO has different pharmacological actions, which are unrelated to its lipid-lowering effects and has the ability to treat chronic airway diseases. This paper reviews the potential of ATO as an anti-inflammatory, antioxidant, and anti-proliferative agent after oral or inhaled administration. This paper discusses the advantages and disadvantages of using ATO under conditions associated with those found in the airways. This treatment could potentially be used to support the formulating of ATO as an inhaler for the treatment of chronic respiratory diseases.